Comparison Of Satisfaction Between Offline Customers And Online Customers At PT Telekomunikasi Seluler Palu - Andi Rifni; Zakiyah Zahara; Ira Nurya Santi; Asriadi Asriadi (UNIVED Press, 2025)
This study aims to analyze the comparison of customer satisfaction levels between online and offline services at PT Telekomunikasi Seluler Palu, specifically for Kartu Halo users. Utilizing a quantitative approach and t-test analysis, the study evaluates six key dimensions of customer satisfaction: expectation-performance alignment, service and product quality, perceived value, customer experience, customer loyalty, and customer feedback. The findings reveal that online services excel in expectation-performance alignment, perceived value, and customer feedback, while offline services outperform in service and product quality, customer experience, and loyalty. However, the overall difference in satisfaction levels between the two services is minimal, indicating that both offer nearly equal quality and are complementary. Additionally, all tested dimensions significantly influence customer satisfaction for both online and offline services. This study provides insights for PT Telekomunikasi Seluler's management to develop more targeted strategies for improving service quality and meeting customer needs effectively.